THE INFLUENCE OF WORKLOAD, DUAL ROLE CONFLICT, AND STRESS ON JOB SATISFACTION AND ITS IMPACT ON THE PERFORMANCE OF FEMALE EMPLOYEES (NURSES) AT PERMATA PAMULANG HOSPITAL - Deanidia, Tiffany; Supratikta, Hadi; Abidin, Ali Zaenal (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of workload, multiple role conflict, and work stress on job satisfaction and their impact on the performance of female employees (nurses) at Permata Pamulang Hospital. The background of this research is based on the hospital’s unmet performance targets, high nursing workloads, the dominance of female employees, and the emergence of conflicts between work demands and family responsibilities that potentially increase stress and reduce job satisfaction. This research adopts a quantitative approach using a survey method. The population consists of all female employees (nurses) at Permata Pamulang Hospital, with a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using path analysis to examine both direct and indirect relationships among variables. The results indicate that workload, multiple role conflict, and work stress have a significant effect on job satisfaction. Furthermore, job satisfaction has a significant effect on employee performance and acts as an intervening variable in the relationship between workload, multiple role conflict, and work stress on performance. These findings suggest that improving nurses’ performance can be achieved through proportional workload management, reducing multiple role conflicts, and controlling work stress to enhance job satisfaction. This study is expected to provide managerial insights for hospital management in formulating human resource policies that emphasize work-life balance and employee well- being.